Optimum water depth for suppressing late watergrass growth with minimizing rice growth inhibition under different temperature conditions - Marina Iwasa; Shunsuke Adachi; Taiichiro Ookawa (Plant Production Science)
Deep-water management (DWM) is a promising approach for effectively suppressing some paddy weeds with reduced use of herbicides. Because DWM for weed control is employed at the initial stage of rice growth, the growth inhibition in rice seedlings occurs by hypoxia. It is worth examining the optimum water control for minimizing rice growth inhibition with effective weed suppression. Here, we evaluated the seedling growth of rice and late watergrass under different water depths (WDs; 5 cm, 10 cm, 15 cm, and 20 cm) and growth temperature (18°C/15°C, 25°C/22°C, and 32°C/25°C of day/night temperature) in the controlled-environment chamber. As growth temperature increased, the WD required for complete suppression of late watergrass increased. A 15 cm or more of WDs completely suppressed the growth of late watergrass under moderate to higher temperature settings, but it significantly decreased the rice growth mainly due to the reduction of tiller number. The follow-up experiment revealed that a stepwise control of WD (10 cm for 3 days and 20 cm for 13 days) could completely suppress the growth of late watergrass without any decrease in rice growth under 32°C/25°C condition. Our findings will contribute to better weed control by DWM in paddy rice cultivation, although further study is needed for application.